Are cash transfers a realistic policy tool for poverty reduction in Sub-Saharan Africa?: Evidence from Congo and Côte d’Ivoire - Hodges, Anthony; Notten, Geranda; O'Brien, Clare; Tiberti, Luca (Université d'Ottawa | University of Ottawa, 2013)
This paper uses evidence from two contrasting African countries, a middle-income oil producer (the Republic of Congo) and a low-income country (Côte d’Ivoire) on the potential role of cash transfers as instruments for poverty reduction and human development. Quantitative simulations of the targeting efficiency, impacts, cost, cost-effectiveness and affordability of different cash transfer options are combined with analysis of political and administrative feasibility. The analysis finds that cash transfers would have more impact on monetary poverty reduction than on human development, while a major practical challenge is to target efficiently in a context of mass poverty. Large-scale cash transfers could be financed domestically in Congo, but this is unlikely in Côte d’Ivoire, and political support is weak in both countries.
Keywords: cash transfers; human development; poverty; social protection; Sub-Saharan Africa